The Use of Technology Tools to Optimize Teacher Talking Time and Enhance Student Engagement (International conference on multidisciplinary science, 2023)
With the increasing integration of technology in education, there is a growing interest in utilizing technology tools to optimize Teacher Talking Time (TTT) and enhance student engagement. This article explores the benefits, challenges, and best practices associated with the use of technology tools in achieving these goals. The benefits include the ability to deliver content in an engaging manner, cater to diverse learning needs, and promote active student participation. However, challenges such as technological distractions and the need for teacher training must be addressed. Best practices include thoughtful tool selection, clear learning objectives, scaffolded instruction, ongoing assessment and feedback, and continuous professional development. By leveraging technology tools effectively, educators can create dynamic learning environments that optimize TTT and enhance student engagement.